A complexidade da disponibilização e acesso a dados governamentais na Web - Moreira, Fábio Mosso [UNESP]; Sant’Ana, Ricardo César Gonçalves [UNESP]; Jorente, Maria José Vicentini [UNESP] (FapUNIFESP (SciELO), 2016)
The Web can be regarded as a promising resource for the sharing of public information. The distribution of government data has been impacted by the governments’ crescent interest in making possible the implementation of web portals to improve efficiency and transparency of their communication actions. Complex features can be observed in the government data distribution process, since data itself does not transmit a message or represent knowledge. This research aims at describing the relation between properties of the Complexity with identified features in the delivery and access processes to government data on the Web, pointing out how these properties can be manifested in the informational flow. By an exploratory study and a literature review, the methodology was based on a qualitative research that identified concepts of Theory of Complex Systems and aspects involved in the sharing of government data on the Web.
Complexity of provision and access of government data in the web
Keywords: Complex System; Complexity; Governmental Data; Web